2022
DOI: 10.3390/met12030456
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Alloying of CoCrFeNiX High Entropy Alloys by Selective Laser Melting

Abstract: High Entropy Alloys are a class of alloys which have been shown to largely exhibit stable microstructures, as well as frequently good mechanical properties, particularly when manufactured by additive manufacturing. Due to the large number of potential compositions that their multi-component nature introduces, high throughput alloy development methods are desirable to speed up the investigation of novel alloys. Here, we explore once such method, in-situ alloying during Additive Manufacture, where a powder of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The optimal energy density depends on the feedstock material used. The effect of volume energy density (VED) on relative density has been investigated by Farquhar et al [ 101 ], as shown in Figure 17 . CrFeCoNi pre-alloyed powder was mixed with Cu powder and Ti powder, and the optimal energy density varied due to differences in the melting points between the CrFeCoNi (1414 °C), Cu (1084 °C), and Ti (1688 °C) powders.…”
Section: Additive Manufacturing (Am) Technologies Of High Entropy All...mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal energy density depends on the feedstock material used. The effect of volume energy density (VED) on relative density has been investigated by Farquhar et al [ 101 ], as shown in Figure 17 . CrFeCoNi pre-alloyed powder was mixed with Cu powder and Ti powder, and the optimal energy density varied due to differences in the melting points between the CrFeCoNi (1414 °C), Cu (1084 °C), and Ti (1688 °C) powders.…”
Section: Additive Manufacturing (Am) Technologies Of High Entropy All...mentioning
confidence: 99%
“… Optical microscopy showing the relative density of three HEA compositions in low, optimal, and high VED (VED values presented in red), Farquhar et al [ 101 ]. …”
Section: Figurementioning
confidence: 99%